IMPLEMENTASI PROGRAM PENGEMBANGAN DAN PEMBERDAYAAN MASYARAKAT USAHA PERTAMBANGAN EMAS PT. PANCA LOGAM MAKMUR DI KABUPATEN BOMBANA PROVINSI SULAWESI TENGGARA - Ardi Ardi; Kamrullah M; Muh Rezeki A.; La Ode Ngkoimani; Irfan Ido; Muhamad Abas; Muhammad Zein Abdullah; La Ode Muhammad Elwan (Universitas Halu Oleo, 2020)
The purpose of this paper is to determine the Community Development and Empowerment Program of PT. Panca Logam Makmur, Bombana Regency with the aim of encouraging the economy, education, socio-culture, health, and the environment of the community around the mine, both individually and collectively. This study uses the Secondary Data Analysis (ASD) method using secondary data, in the form of research data and institutional administrative documentary data. The results of this study are: (1) The realization of the social responsibility of PT. Panca Logam Makmur in 2010-2015 consisted of three main programs, including: (a) community development programs; (b) infrastructure development program; and (c) social welfare action programs; (2) PT. PPM main program plan. Panca Logam Makmur has planned 7 programs or 87.5 percent of the 8 main compulsory PPM programs for metal mineral IUPs; and (3) The implementation of community development and empowerment has not yet compiled a PPM Master Plan which is guided by the PPM blue print for Southeast Sulawesi Province in accordance with Article 57 of the Minister of Energy and Mineral Resources No. 26 of 2018.